PERAN ETIKA AUDIT TERHADAP LAPORAN KEUANGAN PERUSAHAAN : ANALISIS PENGARUH KEDEKATAN EMOSIONAL ANTARA AUDITOR DENGAN KILEN TERHADAP INDEPENDENSI AUDITOR - Ngafifatul Waro (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
In auditing, the attitude of auditor independence is a very important ethical component for auditors. The auditor's task is not only to carry out an audit properly and properly, but the auditor must also be able to maintain professional ethics by instilling an attitude of independence as an auditor. The role of the auditor in an attitude of independence in giving his opinion will be used as a basis when making decisions. The purpose of the authors in making this article is to show how the threat of emotional closeness can affect the quality of audit results if an auditor cannot maintain his independence as an auditor. Researchers used descriptive qualitative methods with a literature study approach. It can be concluded from the results of the analysis that audit judgments should not be based on the auditor's emotional closeness to the client. Efforts to give money, provide entertainment facilities, invest something that could be accepted by the auditor will affect his independence as an auditor. The auditor must understand the right situation in making ethical decisions, in order to continue to produce a good quality audit opinion. Work experience and knowledge as well as self-confidence is sufficient to maintain auditor independence in an audit conflict situation like this.